Cellular cross-talk drives mesenchymal transdifferentiation in diabetic kidney disease - Chatterjee, Arunita; Tumarin, Jacqueline; Prabhakar, Sharma (Frontiers in Medicine, 2025)
While changes in glomerular function and structure may herald diabetic kidney disease (DKD), many studies have underscored the significance of tubule-interstitial changes in the progression of DKD. Indeed, tubule-interstitial fibrosis may be the most important determinant of progression of DKD as in many forms of chronic glomerulopathies. The mechanisms underlying the effects of tubular changes on glomerular function in DKD have intrigued many investigators, and therefore, the signaling mechanisms underlying the cross-talk between tubular cells and glomerular cells have been the focus of investigation in many recent studies. Additionally, the observations of slowing of glomerular filtration rate (GFR) decline and reduction of proteinuria by recent drugs such as SGLT-2 blockers, whose primary mechanism of action is on proximal tubules, further strengthen the concept of cross-talk between the tubular and glomerular cells. Recently, the focus of research on the pathogenesis of DKD has primarily centered around exploring the cross-talk between various signaling pathways in the diabetic kidney as well as cross-talk between tubular and glomerular endothelial cells and podocytes with special relevance to epithelial-to-mesenchymal transition (EMT) and endothelial-to-mesenchymal transition (EndoMT). The focus of this review is to provide a general description of cell-to-cell cross-talk in the diabetic kidney and to highlight these concepts with evidence in relation to the physiology and pathophysiology of DKD.